IDO1-mediated M2 macrophage polarization alleviates the progression of ankylosing spondylitis - Ji, Kangqi; Wang, Lingfei; Liu, Weijie; Li, Genfeng; Lian, Xiaoyu; Fan, Jun; Song, Chen; Jian, Yanpeng (Autoimmunity (Chur, Switzerland), 2025)
Indoleamine 2,3-dioxygenase 1 (IDO1) plays an anti-inflammatory role in autoimmune disease. However, its specific function in ankylosing spondylitis (AS) remain unclear. This study aimed to investigate the potential role of IDO1 in AS. Immunofluorescence, RT-qPCR, and western blot assays were employed to measure gene expression, while ELISA was used to quantify the release of M1 macrophage and M2 macrophage markers. CCK-8, EdU, flow cytometry, ALP staining, and Alizarin red staining (ARS) assays were conducted for functional analysis. JASPAR predicted the binding sites between PPARγ and the promoter, which were further validated by luciferase and ChIP assays. Our findings revealed that the expression of IDO1 was markedly elevated in AS patients. IDO1 overexpression promoted the proliferation of THP-1 cells and M2 macrophage polarization. Conversely, IDO1 knockdown facilitated the osteogenic differentiation of BMSCs. Furthermore, IDO1-mediated upregulation of PPARγ modulated RUNX2 transcription. PPARγ overexpression counteracted the effects of IDO1 knockdown, thereby inhibiting the osteogenic differentiation of BMSCs. In conclusion, the IDO1/PPARγ/RUNX2 signaling pathway may protect against AS by promoting M2 macrophage polarization and inhibiting osteogenic differentiation.